Sediment dynamics of an allogenic river channel in a very arid environment. Issue 11 (20th April 2017) - Yu, Guo‐An; Li, Zhiwei; Disse, Markus; Huang, He Qing
Abstract: Despite a growing interest in the sediment dynamics of dryland rivers, most research has been based on ephemeral streams in endogenic hydrological systems (runoff and sediment transport determined by local precipitation). Less attention, however, has been paid to allogenic and perennial dryland rivers. Here, we report a case study on the suspended sediment dynamics of the Tarim River, an allogenic and perennial river flowing in a very arid environment in China, based on mean daily discharge and mean daily suspended sediment concentration (SSC) over the last 5 decades (1960–2011). Results reveal that discharge and SSCs are predominantly low and have distributions with large positive skewness. The SSC–discharge relationships can be fairly well generalized by power functions, with quite large scatter at extreme (low and high) flow conditions. Marked temporal and spatial variations were observed in the effective discharge for sediment transport. The frequency of the effective discharge ranged from 0.5% to 2% (or an average flow duration of 2–7 days/year), implying that moderate to high flows play an important role in sediment transport. The sediment rating curves show strong hysteresis effects, with 3 types of hysteresis loops observed, clockwise (the most predominant), anticlockwise, and figure of eight. The high potential for bank collapse near the peak and falling limb of the flood hydrograph is the major cause of anticlockwise and figure‐of‐eight hysteresis loops.